2002
DOI: 10.1053/ejvs.2002.1731
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiles in the Acutely Dissected Human Aorta

Abstract: our results demonstrate for the first time the complexity of the dissecting process on a molecular level. The ultimate dissection seems to be the dramatic endpoint of a long-lasting process of degradation and insufficient remodelling of the aortic wall. Altered patterns of gene expression suggest a pre-existing structural failure of the aortic wall, resulting in dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 28 publications
6
55
0
Order By: Relevance
“…Gene expression and gene network analyses revealed that aortic stress first induces a proliferative response, then an inflammatory response in the aortic walls, and finally visible pathological changes. These findings are consistent with findings in human AD 18. Continued aortic stress activates proliferative and inflammatory responses, and these responses occur in parallel with the development of focal medial disruption to the aorta 15.…”
Section: Discussionsupporting
confidence: 91%
“…Gene expression and gene network analyses revealed that aortic stress first induces a proliferative response, then an inflammatory response in the aortic walls, and finally visible pathological changes. These findings are consistent with findings in human AD 18. Continued aortic stress activates proliferative and inflammatory responses, and these responses occur in parallel with the development of focal medial disruption to the aorta 15.…”
Section: Discussionsupporting
confidence: 91%
“…Pathologic studies of acute aortic dissection revealed infiltration of macrophages and leukocytes and increased expression of several genes associated with inflammatory processes, such as interleukin (IL)-6 and IL-8, in the dissected aorta. 18,19 These findings suggested that local aortic insult caused by acute aortic dissection has the potential to produce humoral factors that pass through the pulmonary vasculature and activate both resident leukocytes and the pulmonary vascular endothelium. Sugano et al noted that the powerful insult of intimal rupture and propagation of the dissection into the media might provoke activation of the cellular and humoral inflammatory systems and lead to impaired oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with connective tissue disorders, such as Marfan syndrome, or familial forms of TAA were excluded from these studies, so they do not provide insight into molecular mechanisms of aneurysm progression in these cases. Additionally, no significant gene expression differences were found when tissue from normal and diseased aortic regions were compared from the same TAA patient (9,58), so these studies do not give information about why aneurysms develop in specific vascular locations. Schwill et al (69) investigated changes in aortic gene expression for a Marfan mouse model (mgR) and found increases in inflammatory pathway genes, consistent with our results.…”
Section: Regulated In Fbln4mentioning
confidence: 97%
“…Emr1 and Ptgs2 may represent targets to ameliorate the inflammatory response and limit the diameter expansion in Fbln4 Ϫ/Ϫ AA. It has been shown previously that diseased aortic tissue from TAA patients has different gene expression patterns than normal aortic tissue from control patients (1,9,43,58). Patients with connective tissue disorders, such as Marfan syndrome, or familial forms of TAA were excluded from these studies, so they do not provide insight into molecular mechanisms of aneurysm progression in these cases.…”
Section: Regulated In Fbln4mentioning
confidence: 99%